Dindaadinda Shop / Nur Najihah Mohamad Zaffir and Nur Faradila Azrin Adnan - Mohamad Zaffir, Nur Najihah; Adnan, Nur Faradila Azrin (2021)
Dindaadinda is a business of clothing category that provides hijabs for the ladies located at Ayer Keroh, Melaka. The target of our customer is the Muslim from various segments such as students, employees, and families. Providing the product and delivery services towards the customer and target to achieve the customer satisfaction. The product listed like shawl and ‘bawal’. We offered the gift surprise box for the customer upon request on any occasions such as birthday, engagement and wedding gift. Providing a nice box and ribbon together with a special card from the request and theme given. All products are affordable with various colour provided for each collection. The staff that handle the product and posting service are well trained in order to maintain the quality service. Dindaadinda has the potential to be more successful in the future with a good management and efficiency. To aim the best for the future, we provide a comfortable hijab for us to be the first choice in the market. This can be seen in Muslim who wear the product, will have more confidence in public.